Taiwan's security and air power : Taiwan's defense against the air threat from Mainland China - Edmonds, Martin, 1939-; Tsai, Michael M., 1941- (RoutledgeCurzon security in Asia series., 2004)
This volume brings together a range of experts from the West and from Taiwan itself who examine the key issues connected with Taiwan's air power, which is a key aspect of the China-Taiwan military balance.